Efek Moderasi Dan Mediasi Ambidexterity Organisasi Sebagai Penentu Dalam Meningkatkan Kinerja Pemasaran UMKM - Nurwendi, Wendi; Meutia, Meutia; Lutfi, Lutfi; Haryadi, Didit (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2024)
The purpose of this study is to evaluate and assess the variables that, when combined with modifications to product innovation tactics and customer orientation via ambidexterity, might enhance the marketing performance of MSMEs. The 1,858 MSME implementers in Serang City who own food and beverage MSMEs make up the population of this study. The number of samples acquired using the 10 x 17 indicators was calculated using a purposive sampling method, yielding 170 respondents. Utilizing the SmartPLS Version 4.0 application, the analysis method applies the SEM strategy. The assumption test results indicate that product innovation has a big impact on marketing effectiveness, Organizational ambidexterity and product innovation both have a significant impact on marketing performance. However, the impact of organizational ambidexterity variables on marketing performance is not as strong as that of product innovation, and organizational ambidexterity variables can mediate the effect of market orientation and product innovation on marketing performance. Increasing product innovation and market orientation directly or through organizational ambidexterity are two ways to boost marketing performance.